Syariah Approach Management Model Of the Commision Taken From The Public Donation By Non-Govermental ORganizations (NGOs) - Khadijah Amira Binti Abdul Rashid
In Malaysia, public donation is usually implemented by non-governmental organizations (NGOs). However, there are various issues of accountability and integrity involved in the donation management. This is due to the absence of clear guideline regarding to the commission taken from public donation by the NGOs. The purpose of this research is to study the management aspects of donation fund by NGOs in Malaysia, analyzes the existing law relating to the donation management, analyze types of contracts used and the factors affecting the determination of commission rate. Thus, develop a syariah approach management model of commission taken from the public donation. The methodology used is qualitative method in form of documents analysis and semi-structured interview by involving six selected NGOs in Malaysia who are actively involved in the fundraising activities. The findings show that there are eight management aspects of donation fund applied by the NGO. From a legal perspective, NGOs that registered under Companies Act 2016 only are allowed to spend the donation collection, by referring to the Guideline for Approval of Director General of Inland Revenue under Subsection 44(6) of the Income Tax Act 1967. The guideline stated that at least 50% from the donation received must be spent to achieve the objective of the organization. Meanwhile, the NGOs registered under section 6 of Societies Act 1966 stated that they are not provided with any guideline relating to the commission rate. Besides, there are three three types of Islamic contract applied by the NGO which are ijarah, ji’alah and wakalah. The commission taken is affected by four factors like; i) wage of amil, ii) referring to the syariah law, iii) guideline from mufti, zakah institution and other NGOs and iv) project and management cost. The researcher also suggests seven important elements to the NGO to ensure that it is according to the syariah approach. The impact of this study can be seen from the social aspect by providing solution to the commission rate taken from the donation fund made by the NGOs in Malaysia. In economic aspect, this study helps to strengthen the management of public donation based on the accountability and integrity principles. Indirectly, it supports the implementation of National Anti-Corruption Plan (NACP) (2019-2023) where it promotes transparency, accountability and integrity culture in every Malaysians other than realizing the aim of Shared Prosperity Vision which is providing a decent standard of living for all Malaysians by 2030.